Effect of a Long‐Term Intensive Lifestyle Intervention on Cognitive Function: Action for Health in Diabetes Study. Issue 5 (9th January 2017) - Rapp, Stephen R.; Luchsinger, Jose A.; Baker, Laura D.; Blackburn, George L.; Hazuda, Helen P.; Demos‐McDermott, Kathryn E.; Jeffery, Robert W.; Keller, Jeffrey N.; McCaffery, Jeanne M.; Pajewski, Nicholas M.; Evans, Mary; Wadden, Thomas A.; et al.
Abstract : Objectives: To assess whether randomization to 10 years of lifestyle intervention to induce and maintain weight loss improves cognitive function. Design: Randomized controlled clinical trial. Setting: Data obtained as part of the Action for Health in Diabetes (Look AHEAD) trial (NCT00017953) and Look AHEAD Continuation study (U01 DK057136‐15). Participants: Overweight and obese individuals with type 2 diabetes mellitus aged 45 to 76 (N = 3, 751). Intervention: Intensive lifestyle intervention (ILI) for weight loss through reduced caloric intake and increased physical activity compared with a control condition of diabetes support and education (DSE). Measurements: Certified examiners who were masked to intervention assignment administered a standard battery of cognitive function tests (Modified Mini‐Mental State Examination, Rey Auditory Verbal Learning Test, Digit Symbol Coding, Trail‐Making Test, Modified Stroop Color‐Word Test) to participants 10 to 13 years after enrollment. Results: Assignment to lifestyle intervention was not associated with significantly different overall ( P = .10) or domain‐specific (all P > .10) cognitive function than assignment to diabetes support and education. Results were fairly consistent across prespecified groups, but there was some evidence of trends for differential intervention effects showing modest harm in ILI in participants with greater body mass index and in individuals with a history of cardiovascular disease. Cognitive function was not associated with changes in weight or fitness (all P > .05). Conclusion: A long‐term behavioral weight loss intervention for overweight and obese adults with diabetes mellitus was not associated with cognitive benefit. Trial Registration clinicaltrials.gov Identifier: NCT00017953.